Efect of sewage wastewater reuse of the parameters of growth and nutrition sorgo. - Maria Gabrielle Sousa de Santana (2015)
The wastewater reuse for irrigation crops has many ecological and economic advantages, for example: nutrients recycling, reducing pollution, fertilizer and water economy. Therefore, the reuse of wastewater is an alternative to regions with water deficit, especially in urban and industrial areas. Sorghum is an important crop produced by family farmers in the semiarid region and used in animal feed. Produced under rainfed conditions, the use of irrigation becomes an alternative to stability in production. The research was conducted in EstaÃÃo MeteorolÃgica do Centro de CiÃncias AgrÃrias da Universidade Federal do CearÃ. The effluent used was collected in EstaÃÃo de Tratamento de Esgotos do Campus do Pici (ETE-PICI) da Universidade Federal do CearÃ (UFC), which receives wastewater with sewage characteristics. 10 treatments were used in a completely randomized design with 4 replications. Where: T1 supply water without chemical fertilizers; T2 supply water with 25% of recommended mineral fertilization; T3 supply water with 50% of recommended mineral fertilization; T4 supply water with 75% of recommended mineral fertilization; T5 supply water with 100% of recommended mineral fertilization T6- effluent water without chemical fertilizers; T7- effluent water with 25% of recommended mineral fertilization; T8 effluent water with 50% of recommended mineral fertilization; T9- effluent water with 75% of recommended mineral fertilizer and T10 effluent water with 100% of recommended mineral fertilization. The plant height, stem diameter, number of leaves at 20 days, showed no variation in type of water applied. However, the variables showed significant difference related to the doses of N, P and K. The variables analyzed (Plant height, number of leaves, leaf area, stem diameter) at 40 days after sowing, had significant difference only for the N levels, P and K. The nutrients P and S showed statistical differences in the interaction. The nutrients K and Ca obtained significant results at 1% over the interaction. The nitrogen contents showed a significant difference as the nitrogen rates, P and K, but did not fit any regression model. The treated sewage effluent can be used for irrigation of crops provided a controlled and well managed.